2006
DOI: 10.1038/sj.jcbfm.9600356
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Features of in vivo Skin Microvascular Reactivity in CADASIL

Abstract: CADASIL (Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy) is caused by mutations in the Notch3 receptor expressed at the surface of vascular smooth muscle cells. The functional consequences of the disease at the peripheral microcirculation level are incompletely elucidated. In this study, we aimed to assess, in vivo, the endotheliumdependent and independent vasodilation of the skin microvasculature in CADASIL patients. Twentythree affected subjects were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
2
23
4
Order By: Relevance
“…Vasodilation of a conduit vessel, the brachial artery, was similar in patients and controls, which is also in agreement with a previous study. 20 However, the present study showed a reduction in both resting and hyperemic forearm blood flow in the forearm of CADASIL patients compared with the controls. This difference in hyperemic blood flow was only significant for the highest dose of acetylcholine.…”
Section: Discussioncontrasting
confidence: 42%
“…Vasodilation of a conduit vessel, the brachial artery, was similar in patients and controls, which is also in agreement with a previous study. 20 However, the present study showed a reduction in both resting and hyperemic forearm blood flow in the forearm of CADASIL patients compared with the controls. This difference in hyperemic blood flow was only significant for the highest dose of acetylcholine.…”
Section: Discussioncontrasting
confidence: 42%
“…Experimental studies revealed that in response to mechanical stress VSMC synthesizes abundant amount of matrix proteins, mostly collagen [6]. Since in CADASIL mechano reactivity of vessels is disturbed [7][8][9], it is possible that normal levels of vascular tension can be interpreted by VSMC as too high and, like in the case of arterial hypertension, it can initiate cascade of reactions leading to vessel fibrosis. It is known that collagen stimulates phenotypic changes in VSMC towards the synthetic phenotype [10] more vulnerable for apoptosis [11] especially when VSMC are submitted to mechanical stress [12].…”
Section: Discussionmentioning
confidence: 99%
“…Skin vasoreactivity is altered in disease. For instance, the kinetics of reactive hyperemia after cuff occlusion displays a delayed and slow curve 17 . Endothelium-dependent vasodilation is impaired in resistance arteries (not conductive ones) in the forearm of patients 18 .…”
Section: Genetics and Pathogenesismentioning
confidence: 99%